Cross‐Coupling Reaction of a Highly Strained Molecule: Synthesis of σ–π Conjugated Tetrahedranes1. Issue 41 (26th August 2013) - Kobayashi, Yuzuru; Nakamoto, Masaaki; Inagaki, Yusuke; Sekiguchi, Akira
<x xml:space="preserve">Abstract</x> Strain for an effect: The cross‐coupling reaction of highly strained tetrahedranes with aryl halides has been investigated. In the presence of a palladium catalyst, tetrahedryllithium rapidly reacted with various aryl halides to form aryl‐substituted tetrahedranes (see picture) in good to excellent yields. The UV/Vis absorption spectra suggest an extended σ–π conjugation between the σ orbital of the tetrahedrane core and the aryl π system.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>